REPRESENTATION OF ASEPTIC LOCATIONS IN THE CONTEXT OF CLASS DIFFERENCES: SAMPLE OF HABITATION ADS - Alpman, Polat S; Göker, Göksel (Akdeniz Üniversitesi, 2010)
Modern structural forms noticed in urban life, play an important role to emphasize the class differences. Certain areas of the city with their modern habitat are pertained to a special social class and that triggers exclusion of other class properties. Residence areas are the most distinctive example of this case. While residence determines the way of living, it also refers to class differences and serves to rise of that difference. In this regard, residence areas are isolated and purified from others in order to claim that they are aseptic. Residences have tendency to differentiate themselves from classical meaning of housing with branding. Therefore residence living areas are often subject to ads. In this study, aseptic locations shaped in the context of class differences are examined. Main object of this study is to examine if the residence areas are used as a medium to emphasis the differences, diverging from context of classical housing. With this aim, semiotic analysis is employed in order to analyze the three newspaper ads reflecting the typical characteristics of residence areas

Kent yaşamı içerisinde göze çarpan modern yapılanma şekilleri sınıfsal farklılıkların vurgulanmasında önemli bir işlev üstlenmektedir. Kentin belli bölgeleri, içerisinde barındırdığı modern yaşam alanları ile bir sınıfa has kılınırken, diğer sınıfsal özelliklerin dışarıda kalmasına neden olmaktadır. Bu durumun en çarpıcı örneğini rezidans alanları teşkil etmektedir. Rezidans bir yaşam alanı olarak kurgulanırken, aynı zamanda sınıf farklılıklarına gönderme yapar ve bu farklılıkların derinleşmesine hizmet eder. Bu yönüyle kendini diğerlerinden ayıran ve arındıran rezidans alanları aseptik olma iddiasını gerçekleştirir. Rezidans, klasik anlamda konut olgusundan da kendini başkalaştırarak, markalaşma eğilimi göstermektedir. Bu sebeple rezidans yaşam alanları sık sık reklamlara konu olmaktadır. Bu çalışmada, sınıf farklılıkları bağlamında şekillenen aseptik mekanlar incelenmektedir. Çalışmanın ana fikri, rezidans alanlarının konut ve barınma bağlamından koparılarak farklılıkların vurgulanmasında bir araç olarak kullanıldığı düşüncesine dayanmaktadır. Bu amaçla, çalışma kapsamında rezidans alanlarının tipik özelliklerini yansıtan üç gazete reklamının göstergebilimsel analizi yapılmıştır
SINIFSAL FARKLILIKLAR BAĞLAMINDA ASEPTİK MEKANLARIN TEMSİLİ: KONUT REKLAMLARI ÖRNEĞİ